First-principles calculation of Sb2Te3 topological insulator under pressure. (2021) - Pal, Debarati; Patil, Swapnil; Chatterji, Sandip
Abstract: The theoretical density of states (DOS) along with band structure (BS) has been evaluated for Topological insulator Sb2 Te3 upon pressure. The density functional theory (DFT) calculation shows electronic topological transition (ETT) under the application of pressure. When pressure is applied conduction band and valence shifts significantly which is indicated as electronic transition of the Fermi surfaces. The band gap between conduction band and valence band reduced at Z-high symmetry point whereas it is observed to enhance at Γ-point with increase in pressure. Interestingly, we found semiconductor to metal transition near 2 GPa with LDA approximation. The overall change in the Fermi surfaces is found to follow other topological materials like Bi2 Te3, Sb2 Se3 and Bi2 Se3 . The topologically non-trivial surface state remains unchanged under pressure; however, the bulk band gap reduces.